Thermoreversible Self‐Healing Networks Based on a Tunable Polymethacrylate Crossslinker Having Pendant Maleimide Groups. Issue 19 (2nd August 2016) - Arunbabu, Dhamodaran; Noh, Seung Man; Nam, Joon Hyun; Oh, Jung Kwon
Abstract : Self‐healable crosslinked networks able to effectively repair physical damages with no needs of extra healing agents have been developed as effective building blocks in constructing high‐performance industrial and biomedical materials. Here, the development of novel polymer‐based crosslinked materials exhibiting thermally induced self‐healability is reported. The new approach centers on the design and synthesis of polymethacrylates having tunable densities of pendant furan‐protected maleimide groups (PMIMA) as multivalent crosslinkers using a controlled polymerization. Upon the loss of furan protecting groups at elevated temperatures, the PMIMA involves covalent crosslinking with polymethacrylates bearing pendant furan groups in reactive blends. The resulting crosslinked networks exhibit greater thermal stability as well as self‐healability through thermoreversible Diels‐Alder/Retro Diels‐Alder chemistry, offering versatility in surface‐protective coatings. Abstract : Development of a new approach that centers on the design and synthesis of novel polymethacrylates having tunable densities of pendant furan‐protected maleimide groups as multivalent crosslinkers for the development of crosslinked networks, exhibit greater thermal stability as well as self‐healability through thermoreversible Diels‐Alder/Retro Diels‐Alder chemistry, thus offering versatility in surface‐protective coatings.